Growth determinants of handicraft industry in sri lanka: view on progressive factor conditions - Sachitra, V.; Wijeratne, A.S. (University of Jaffna, 2022)
Purpose: The handicraft industry in Sri Lanka is an interesting industry coming from the past which is mostly attracted by the tourists who travel in Sri Lanka. The main objective of this study is to investigate the growth determinants of the firms in the handicraft industry in Sri Lanka. Methodology: The study used the deductive approach; following the survey method to collect data from 180 handcrafters. Acknowledging the progressive factor conditions in Porter's Diamond model, knowledge; experience; technology; infrastructure facilities; and training factors selected as the growth determinants. Findings: Multiple regression results revealed that knowledge (b = 0.43), technology (b = 0.37), and infrastructure facilities (b = 0.13) have a significant and a positive influence on the growth of the handicraft business. However, experience and training were not significant factors conditions to the growth of the handicraft. Implications: Handicraft industry is a major source of income for rural communities and it is a fast-growing industry in Sri Lanka. Results imply that the government and the responsible authorities should provide more concern to invest on new technological innovations, training facilities and supportive services such as IT facilities, export facilities and so on. Attracting youth participation into the industry needs vital attention. Future researchers can go upon random larger sample of handcrafters from various geographical locations to provide more generalizable results.
Keywords: Growth; Handicraft industry; Human resources; Technology; Training